Supporting group interactions in museum visiting - Tolmie, Peter; Benford, Steve; Greenhalgh, Chris; Rodden, Tom; Reeves, Stuart (2014)
Ethnographic study in two contrasting museums highlights a widespread but rarely documented challenge for CSCW design. Visitors' engagement with exhibits often ends prematurely due to the need to keep up with or attend to fellow group members. We unpack the mechanics of these kinds of phenomena revealing how the behaviours of summoning, pressurizing, herding, sidelining, and rounding up, lead to the responses of following, skimming and digging in. We show how the problem is especially challenging where young children are involved. As an initial prompt we explore two ways in which CSCW could help address this challenge: enabling a more fluid association between information and exhibits; and helping reconfigure the social nature of visiting.